Relaciones entre los parámetros físico-químicos del suelo y la vegetación en juncales de Scirpoides holoschoenus - Cantó, Paloma; Molina, José Antonio; García-Madrid, Ana S.; Casermeiro, Miguel Angel; Cruz, Mª Teresa De La (Lazaroa, 2011)
A study of Scirpoides holoschoenus rushes was carried out in the centre of the Iberian Peninsula. This study was based on 54 phytosociological relevés collected from the literature, and on 17 of our own surveys in which we analyze the species composition of vegetation and the main physico-chemical soil parameters. Numerical analysis shows the existence of four associations: Holoschoenetum vulgaris, Lysimachio ephemeri-Holoschoenetum, Holoschoeno-Juncetum acuti and Trifolio resupinati-Holoschoenetum. In addition, we confirm the existence of two groups of Scirpoides holoschoenus rushes in the central Iberian peninsula based on the soil soluble-ion content, whether calcareous or silicicolous. The uncertain adscription of sub-halophilous rushes to one or another group suggests that several units may exist within them.
Keywords: Rush meadows; Tagus River; Vegetation; Soil parameters